2003
DOI: 10.1152/ajpcell.00568.2002
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of cellular communication among thymic epithelial cells: intercellular calcium wave propagation

Abstract: We here describe intercellular calcium waves as a novel form of cellular communication among thymic epithelial cells. We first characterized the mechanical induction of intercellular calcium waves in different thymic epithelial cell preparations: cortical 1-4C18 and medullary 3-10 thymic epithelial cell lines and primary cultures of thymic "nurse" cells. All thymic epithelial preparations responded with intercellular calcium wave propagation after mechanical stimulation. In general, the propagation efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 67 publications
1
24
0
2
Order By: Relevance
“…Confirming previous results from our Laboratory [39,61,62] flow cytometry experiments revealed that after 6 hours of co-culture more than 65% of the initial single positive DiIc 18 (3) + TEC acquired calcein (Figure 1B). To ascertain that gap junctions mediated this dye transfer we treated the cells for 6 hrs with 100 μM of 18-β-glycyrrhetinic acid (GRA), a gap junction inhibitor.…”
Section: Resultssupporting
confidence: 91%
“…Confirming previous results from our Laboratory [39,61,62] flow cytometry experiments revealed that after 6 hours of co-culture more than 65% of the initial single positive DiIc 18 (3) + TEC acquired calcein (Figure 1B). To ascertain that gap junctions mediated this dye transfer we treated the cells for 6 hrs with 100 μM of 18-β-glycyrrhetinic acid (GRA), a gap junction inhibitor.…”
Section: Resultssupporting
confidence: 91%
“…Subsequently, ICWs have been found to be initiated by a variety of stimuli in a diversity of cell types, including glial cells (246,312,361), neurons (56, 153), various epithelial (171,249) and endothelial (47,129,382) cells, smooth muscle cells (151, 407), cardiomyocytes (352), hepatocytes (122), osteocytes (178), chondrocytes (189), kidney cells (276,402), mammary gland cells (104), mast cells (255), pancreatic acinar cells (409), and keratinocytes (188). FIGURE 1 illustrates typical examples of ICWs in glial and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated the involvement of gap junctions in the communication between cells of the immune system [17][18][19][20][21][22][23][24]. Indirect evidence for the importance of gap junctions in immunity comes from the observation that viruses -such as herpes simplex virus (HSV) and human papillomavirus (HPV) -actively influence gap junction communication [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%